The Current State of the Teaching of Programming Languages in "Information and Information Technology" in European General Secondary Schools. - Jumanqo‘ziyev O‘ktamjon O‘tkirjon o‘g‘li (Zien Journals, 2022)
The article analyzes the regular teaching of modern programming languages in secondary schools of European countries
Keywords: Algorithm basics and programming; Programming language; Pascal; Python